A generally neglected threat in infant nutrition: incorrect preparation of infant formulae - Egemen, Ayten; Kusin, Nesrin; Akşit, Sadık; Emek, Mestan; Kurugöl, Zafer (The Turkish Journal of Pediatrics, 2002)
Breast milk is the most appropriate food for infants. At least 4-6 months of breast feeding is sufficient for all babies if appropriate growth is monitored monthly. However, for those infants unable to breast-feed sufficiently or at all, formula can be given as an alternative. However, serious health problems such as hypernatremic dehydration, malnutrition, and obesity may develop if powdered formula is not appropriately prepared. In the present study, our aim was to investigate whether or not mothers of formula-fed babies in Özkanlar (İzmir, Turkey) district prepared powdered infant formula appropriately. For this purpose, we visited all (328) families with infants younger than 12 months of age. Forty-two (13%) of these 328 infants were still fed formula. The mothers of the infants were asked to prepare formula for two different meals, and duplicate samples from each prepared formula were taken for the measurement of dry matter. Fifty percent of the mothers diluted formula with 10% more or 10% less water for the second meal as compared with the first meal. Four (10%) mothers diluted formula with 10% or less of the required water, while 27 (64%) prepared formula with 10% or more of the required water. It is concluded that mothers must be informed about the preparation of formula when formula is prescribed for their babies.